Maslow and Al-Ghazali's Hierarchy of Needs Theory is an Implementation of Sharia Maqashid to the Perspective of Islamic Economics - Riski Murdani; Al-Amin; Hadi Subeno; Fahmi Sulaiman (Universitas 17 Agustus 1945 Semarang, 2024)
The main objective of Maqashid Shari'ah is to protect and fight for three legal categories, namely among others are Dharuriyat, Hajjiyat and Tahsiniyat. And there are five basic important elements namely soul (Hifdzunnafs), belief or religion (Hifdzuddin), reason/intellectual (Hifdzul Aql), descent (Hifdzunasl) and family and property (Hifdzulmal). The research objective is to look at the advantages and disadvantages between Maslow's and Al-Ghazali's Hierarchy of Needs in Islamic Economics. The research method is library research using primary and secondary data, namely books and scientific journals. The results of this study are Al-Ghazali's theory of needs which is almost parallel to Maslow's subsequent theory. Meanwhile, of the five elements, Maslow's theory of needs and al-Ghazali's are related to each other and there are also similarities, but al-Ghazli is more dominant in explaining the theory of these needs.